al-Awza'i and Umayyad Influence on Islamic Legal Development - Judd, Steven (The Umayyad World, 2020)
The Umayyad World encompasses the archaeology, history, art, and architecture of the Umayyad era (644–750 CE). This era was formative both for world history and for the history of Islam. Subjects covered in detail in this collection include regions conquered in Umayyad times, ethnic and religious identity among the conquerors, political thought and culture, administration and the law, art and architecture, the history of religion, pilgrimage and the Qur’an, and violence and rebellion. Close attention is paid to new methods of analysis and interpretation, including source critical studies of the historiography and inter-disciplinary approaches combining literary sources and material evidence. Scholars of Islamic history, archaeologists, and researchers interested in the Umayyad Caliphate, its context, and infl uence on the wider world, will find much to enjoy in this volume.
Keywords: dept.his

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge studies in modern history, 2020)
Keywords: Causes; Historiography; Historiography; World War, 1914-1918; World War, 1914-1918; dept.his; faculty_collection

Western Science in Indochina, 1800-1998 - Thompson, C Michele (The Cambridge History of Science Vol. 8, Modern Science in National and International Context, 2020)
Keywords: dept.his

Storm of the Sea: Indians & Empires in the Atlantic's Age of Sail - Smith, Jason W. (Journal of American Studies, 2020)
Keywords: dept.his; peer-reviewed

Preserving Maritime America: A Cultural History of the Nation's Great Maritime Museums - Smith, Jason W. (New England Quarterly-a Historical Review of New England Life and Letters, 2020)
Keywords: dept.his

Guatemala's Catholic Revolution: A History of Religious and Social Reform, 1920-1968. - Kordick, Carmen (Americas, 2020)
Keywords: dept.his; peer-reviewed

They're going to kill me there. Culture, violence and the Cold War in Costa Rica (1979-1990) - Kordick, Carmen (Americas, 2020)
Keywords: dept.his; peer-reviewed

Indochina - Thompson, C. Michele (Cambridge History of Science, Vol 8: Modern Science in National, Transnational, and Global Context, 2020)
Keywords: dept.his

The Rumble in the Jungle: Muhammad Ali and George Foreman on the Global Stage - Rondinone, Troy (Journal of American History, 2020)
Keywords: dept.his; peer-reviewed

The russian holy synod and the greeks: Reconsidering greek-russian relations in the early modern period (16th–18th centuries) - Chrissidis, Nikolaos A. (Canadian-American Slavic Studies, 2020)
The article first surveys Greek interpretations of the creation of the Russian Holy Synod by Peter the Great. It provides a critical assessment of the historiographical paradigm offered by N.F. Kapterev for the analysis of Greek-Russian relations in the early modern period. Finally, it proposes that scholars should focus on a Greek history of Greek-Russian relations as a complement and possibly corrective to the Kapterev paradigm. © verlag ferdinand schöningh, 2020.
Keywords: Aleksander stourdza; Greek-russian relations; Konstantin oinonomos; Nikolai kapterev; Peter the great; Russian holy synod; dept.his; peer-reviewed

The threat from the east - Paddock, Troy (The Central Powers in Russia's Great War and Revolution, 1914-22: enemy visions and encounters, 2020)
"This multiauthor collection of essays analyzes Russia's Great War and Revolution from the perspective of the Central Powers and their encounters with Russia and the Revolution. The peoples of the Central Powers, from elites to civilians, understood the violent clash of armies in a variety of ways. Essays highlight the variety of military and civilian experiences and deal with topics of how soldiers, civilians, and intellectuals perceived Russia and how these understandings translated into security goals, utopian plans for conquered territories, and interethnic violence."--
Keywords: 1894-1917; 20th century; Central Powers (1914-1918); Europe, Eastern; Historiography; History; History, Military; Politics and government; Revolution, 1917-1921; Russia; Soviet Union; World War, 1914-1918; dept.his